Role of SLC5A8, a plasma membrane transporter and a tumor suppressor, in the antitumor activity of dichloroacetate - Babu, Ellappan (2011)
There has been growing interest among the public and scientists in dichloroacetate as a potential anticancer drug. Credible evidence exists for the antitumor activity of this compound, but high concentrations are needed for significant therapeutic effect. Unfortunately, these high concentrations produce detrimental side effects involving nervous system, thereby precluding its use for cancer treatment. The mechanistic basis of the compound’s antitumor activity is its ability to activate pyruvate dehydrogenase complex through inhibition of pyruvate dehydrogenase kinase. Since the compound inhibits the kinase at micromolar concentrations, it is not known why therapeutically prohibitive high doses are needed for suppression of tumor growth. We hypothesized that lack of effective mechanisms for the entry of dichloroacetate into tumor cells may underlie this phenomenon. Here we show that SLC5A8 transports dichloroacetate very effectively with high affinity. This transporter is expressed in normal cells, but the expression is silenced in tumor cells via epigenetic mechanisms. The lack of the transporter makes tumor cells resistant to the antitumor activity of dichloroacetate. However, if the transporter is expressed in tumor cells ectopically, the cells become sensitive to the drug at low concentrations. This is evident in breast cancer cells, colon cancer cells, and prostate cancer cells. Normal cells, which constitutively express the transporter, are however not affected by the compound, indicating the tumor cell-selective therapeutic activity. The mechanism of the antitumor activity of the compound is still its ability to inhibit pyruvate dehydrogenase kinase and force mitochondrial oxidation of pyruvate. Since the silencing of SLC5A8 in tumors involves DNA methylation and its expression can be induced by treatment with DNA methylation inhibitors, our findings suggest that combining dichloroacetate with a DNA methylation inhibitor would offer a means to reduce the doses of dichloroacetate to avoid detrimental effects associated with high doses but without compromising antitumor activity.